A Four-MicroRNA Panel in Serum as a Potential Biomarker for Screening Renal Cell Carcinoma - Li, Rongkang; Lu, Chong; Li, Xinji; Chen, Xuan; Huang, Guocheng; Wen, Zhenyu; Li, Hang; Tao, Lingzhi; Hu, Yimin; Zhao, Zhengping; Chen, Zebo; Lai, Yongqing (Frontiers in Genetics, 2022)
Background: Renal cell carcinoma (RCC) has been a major health problem and is one of the most malignant tumors around the world. Serum microRNA (miRNA) profiles previously have been reported as non-invasive biomarkers in cancer screening. The aim of this study was to explore serum miRNAs as potential biomarkers for screening RCC. Methods: A size of 220 participants (108 RCC patients and 112 normal controls (NCs)) were enrolled for conducting a three-phase study. In the screening phase, 12 candidate miRNAs related RCC were selected for further study by ENCORI database with 517 RCC patients and 71 NCs. The dysregulated candidate miRNAs were further confirmed with 30 RCC patients and 30 NCs in the training phase, and with 78 RCC patients and 82 NCs in validation phase. Receiver operating characteristic (ROC) curves and the area under the ROC curve (AUC) were used for assessing the diagnostic value of miRNAs. Bioinformatic analysis and survival analysis were also included in our study. Results: Compared to NCs, 6 miRNAs (miR-18a-5p, miR-138-5p, miR-141-3p, miR-181b-5p, miR-200a-3p and miR-363-3p) in serum were significantly dysregulated in RCC patients. A four-miRNA panel was built by combining these candidate miRNAs to improve the diagnostic value with AUC=0.908. ABCG1 and RNASET2, considered as potential target genes of the four-miRNA panel, may play significant role in the development of RCC. Conclusions: A four-miRNA panel in serum was identified for RCC screening in our study. The four- miRNA panel has a great potential to be non-invasive biomarkers for RCC screening.